Organic cation transporter 3 (OCT3/SLC22A3) and multidrug and toxin extrusion 1 (MATE1/SLC47A1) transporter in the placenta and fetal tissues: expression profile and fetus protective role at different stages of gestation - Ahmadimoghaddam, Davoud; Zemankova, Lenka; Nachtigal, Petr; Dolezelova, Eva; Neumanova, Zuzana; Cerveny, Lukas; Ceckova, Martina; Kacerovský, Marian; Micuda, Stanislav; Staud, Frantisek (Biology of reproduction, 2013)
In our previous study, we described synchronized activity of organic cation transporter 3 (OCT3/SLC22A3) and multidrug and toxin extrusion 1 (MATE1/SLC47A1) transporter in the passage of organic cations across the rat placenta and the role of these transporters in fetal defense; in this study, we hypothesized that changes in placental levels of OCT3 and MATE1 throughout gestation might affect the fetal protection and detoxification. Using quantitative RT-PCR, Western blot analysis, and immunohistochemistry, we were able to detect Oct3/OCT3 and Mate1/MATE1 expression in the rat placenta as early as on Gestation Day (gd) 12 with increasing tendency toward the end of pregnancy. Comparing first versus third trimester human placenta, we observed stable expression of OCT1 and decreasing expression of OCT2 and OCT3 isoforms. Contrary to the current literature, we were able to detect also MATE1/MATE2 isoforms in the human placenta, however, with considerable inter- and intraindividual variability. Using infusion of 1-methyl-4-phenylpyridinium (MPP(+)), a substrate of OCT and MATE transporters, into pregnant dams, we investigated the protective function of the placenta against organic cations at different gds. The highest amount of MPP(+) reached the fetus on gd 12 while from gd 15 onward, maternal-to-fetal transport of MPP(+) decreased significantly. We conclude that increased expression of placental OCT3 and MATE1 along with general maturation of the placental tissues results in significantly lower transport of MPP(+) from mother to fetus. In contrast, decreasing expression of OCT3 and MATE1 in human placenta indicates these transporters may play a role in fetal protection preferentially at earlier stages of gestation.
Keywords: Pregnancy; proteiny přenášející organické kationty; Rats, Wistar; Placenta; vývoj plodu; Animals; potkani Wistar; antiportéry; Humans; Immunohistochemistry; Female; krysa rodu Rattus; Fetus; Rats; přenašeče organických aniontů nezávislé na sodíku; ženské pohlaví; Fetal Development; RNA, Messenger; Antiporters; placenta; zvířata; Organic Cation Transport Proteins; western blotting; plod; imunohistochemie; Blotting, Western; lidé; těhotenství; Organic Anion Transporters, Sodium-Independent; messenger RNA